The role of a nurse and a midwife in vaccinations of children and adolescents - Stefanowicz, Anna; Krajewska, Maria; Kołodziejska, Aneta; Wierzba, Jolanta (Polish Journal of Public Health, 2012)
Nowadays nurses and midwives are autonomous workers of the health care system. They pursue their goals with independence and responsibility. While carrying out their professional duties towards patients, they provide them with care, education and health promotion, as well as perform prophylactic, therapeutic and rehabilitative functions. They also actively participate in public health issues. In accordance with the World Health Organization (WHO) suggestions, public health is a domain of knowledge and skills, where the prevention against diseases, the prolongation of human life and the promotion of physical and mental health are the objectives. Prophylactic vaccinations are one of the greatest achievements of public health. A prophylactic vaccination is the introduction of a vaccine into the human or animal organism to produce humoral and/or cellular immunity. Vaccine is a preparation containing an antigen or antigens, used to produce active immunity. The first vaccine in the world was invented by an English physician Edward Jenner. It was a vaccine against smallpox. Vaccinations in Poland can either be mass-scale or individual operations. These vaccinations are performed on the basis of the Immunization Programme, announced by the Chief Sanitary Inspectorate (Główny Inspektorat Sanitarny) for a given year. In accordance with the Polish legislation, some of the prophylactic vaccinations are obligatory, while others only recommended. Prophylactic vaccinations can be administered by nurses and those midwives who underwent a special training. This paper presents the division, objectives, indications, contraindications, general principles, techniques and conditions of vaccinations; it also describes the roles of nurses and midwives in administering prophylactic vaccinations to children and adolescents.